Chest Injury Outcomes due to Road Traffic Accidents – an Institutional Experience - Amit Chaudhary1, Amit Singh2 , Roopak Aggarwal3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background -Thoracic trauma is one of the leading causes of mortality and morbidity in developing worldcountries. Complications in chest trauma develop secondary to rib fractures and subsequently leading topain, inadequate ventilation as well as direct injury to lung parenchyma due to fractured rib segments.Methods - In this study, we present our 2 year experience (August 2017 to August 2019) in the managementand clinical outcome of 236 chest trauma cases as a result of road traffic accidents. Patients were dividedinto three groups based on the presence of rib fractures. The groups were evaluated to demonstrate therelationship between the numbers of rib fractured and associated injuries.Results – Mean hospitalization time was 7.5 days. Mortality rate was 1 % for the patients with only bluntchest trauma, 4 % in patients with more than two rib fractures and 20 % for those with flail chest. We foundthat there is significant association between the mortality rate and the number of ribs fractured, the patient’sage as well time since the accident.Conclusion – Risk of increased morbidity and mortality was associated with presence of more than two ribfractures, age over 60 years and delayed hospitalization after the injury